Investigation of Fair Play Behaviors of Secondary School Students Participating in School Sports - İbrahim Umran Akdağcık; Ahmet Temel (Türk Spor ve Egzersiz Dergisi, 2023)
This research aims to examine the fair play behaviors of secondary school students who participate in school sports. The sample of the research consists of 495 secondary school students who continue their education in Niğde in the 2022-2023 academic year and are selected by purposive sampling method. “Frequency of Exhibiting Fair Play Behaviors Scale” was used as a data collection tool in the research. Descriptive statistics, t-tests, and ANOVA tests were performed in the analysis of the data, and a significance level of .05 was taken into account in the interpretation of the data. According to the research findings, the students who participated in school sports exhibited fair play behavior at a frequent level in the spectator dimension; at a very frequent level in team, negative behavior, opponent dimension, throughout the scale. Fair play behaviors of female students were higher than male students. According to the grade level, the scores of the 5th-grade students were found to be significantly higher than the 7th-grade students. While the fair play behaviors of the students playing football in the spectator dimension of the scale were higher than the athletes interested in individual branches, no significant difference was found in other dimensions. In the variable of sports age, the fair play behaviors of the students who do sports for 1-3 years were found to be higher than the students who did sports for less than 1 year. As a result of the research, it has been determined that secondary school students participating in school sports exhibit fair play behaviors very often and develop more positive attitudes towards their team. It is recommended that secondary school students participate in events such as games, competitions, and tournaments within the scope of school sports.